Tirana modern : biblio-ethnography on the margins of Europe - Rosen, Matthew, 1977- (Vanderbilt University Press, 2022)
"The book tells a story of Albanian modernity from the perspective of the author's participation in the daily lives of two avid readers living in Tirana"--